TEMPERATURE VARIATION IN APPLICATION OF ARTIFICIAL NEURAL NETWORK FOR PREDICTION OF CORROSION RATE UNDER INSULATION - BURHANI, NURUL RAWAIDA AIN (2018)
Corrosion under insulation (CUI) in pipes is increasingly becoming an important issue in the industry due to the prevalence of unexpected explosion and incidents as the result of undetectable CUI due to its hidden nature. As for these reasons, continuous CUI monitoring is indispensable to ensure that the CUI rate occurrence can be measured and be used for inspection.